Optimization of a reinforced geopolymer composite using natural fibers and construction wastes - Silva G. (2020)
Geopolymer technology has allowed the development of eco-friendly construction materials with high mechanical properties using industrial wastes and residues. However, geopolymers show fragility and low ductility behavior similar to Portland cement-based materials. This article focuses on the evaluation of jute and sisal fibers as reinforcement of a geopolymer matrix produced from residues of Fired Clay Brick Powder (FCBP). Control samples with no fibers and reinforced matrices with different contents of jute (ranging from 0.5 to 2.0 wt%) and sisal fibers (ranging from 0.5 to 3.0 wt%) were produced to study the effect of the fiber type and content on the mechanical properties of the resulting geopolymer composites. Mechanical characterization consisted of compression, splitting tensile, and three-point bending tests. The results of compression and splitting tensile tests showed the existence of an optimum fiber content that depends on the fiber type for reaching the maximum strength while the three-point bending test results indicated a linear relationship between the flexural strength and the fiber content. The addition of 2.5% (wt%) of sisal fibers increased the compressive, splitting tensile and flexural strengths up to 76%, 112%, and 270%, respectively, in comparison to the control samples. On the other hand, FCBP-based geopolymers with 1.5% (wt%) jute fiber reinforcement showed an increase up to 64%, 45%, and 222% of the compressive, splitting tensile and flexural strengths, respectively. Both, jute and sisal fiber addition at the optimum content, lead to a change in the failure mode of the samples from a brittle to a more ductile failure in all mechanical tests. © 2020 Elsevier Ltd